PENGARUH KEJELASAN SASARAN ANGGARAN, PENGENDALIAN AKUNTANSI, DAN SISTEM PELAPORAN TERHADAP AKUNTABILITAS KINERJA INSTANSI PEMERINTAH (Studi pada Satuan Kerja Perangkat Daerah Kabupaten Bengkalis) - Siti Ruri Suhaesti; Hardi '; Al-Azhar A ' (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2016)
This study aims to determine the effect of budget goal clarity , Accounting Control and Reporting System on performance accountability of public Institutions in bengkalis. The research uses a survey of the work unit bengkalis district. The population in this study was 34 SKPD in Bengkalis .The sampling technique is purposive sampling technique. Data analysis techniques to test hypotheses using multiple analytical approach. The results showed that the influential Budget Targets Clarity with tcount > ttable 2.155 > 1.663 , Control Accounting significant effect with the value tcount > ttable 2.456 > 1.663 , significant effect Reporting System with the value tcount > ttable 2,166 > 1,663 terhadap Accountability Government Agencies performance . While the R -square value that is equal to 0,645, which means 64.5 % of the independent variable in this study could affect the dependent variable. While the remaining 35.5 % is influenced by other variables not examined in this study such as leadership styles, organizational culture budget participation, the application of accounting information, organizational commitment.Keywords: budget goal clarity, control accounting, reporting system, and performance accountability.